Comparing information technology adoption between developing and developed countries - Nourbakhsh, Mehdi (American Society of Civil Engineers, 2012)

(untitled)
Information technology adoption is critically important because it is a fundamental element of successful project management. Although some studies have been carried out to investigate the use of information technology in the construction industry, there is no comprehensive literature to compare the information technology adoption among different countries. This research aims at investigating the current extent of information technology use between developing and developed countries. To achieve this aim, a questionnaire was sent to 800 construction professionals from 20 countries. From those, 151 completed and reliable responses were selected to be analyzed. The result of the research reveals that there is no significant difference between developing and developed countries in information technology adoption; however, developed countries are more advanced in information technology use compared to developing countries. The results of this study are useful to provide directions in research, training, and development of strategies that will respond to the needs of the construction industry in the area of information technology selection.